2017
DOI: 10.21470/1678-9741-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine versus Dopamine to Prevent Acute Kidney Injury after Cardiac Surgery in Patients with Preexisting Moderate Renal Insufficiency

Abstract: ObjectiveAcute kidney injury after cardiac surgery is associated with mortality and morbidity. Therefore, strategies to prevent acute kidney injury are very important. The aim of this placebo-controlled randomized double-blind study was to compare the prophylactic efficacy of N-Acetylcysteine and dopamine administration in patients with pre-existing moderate renal insufficiency who were undergoing cardiopulmonary bypass.MethodsThis study included 135 patients with pre-existing moderate renal insufficiency who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
(10 reference statements)
2
11
0
Order By: Relevance
“…Patients who developed AKI were older and had higher BMI, hypertension, severe left ventricular dysfunction, and worse preoperative renal function. Our findings aligned with the current data which report the etiology of AKICS as multifactorial [ 24 - 26 ] , correlating with advanced age, preexisting kidney disease, and left ventricular impairment, which are some of the important predictors of AKI development [ 20 ] .…”
Section: Discussionsupporting
confidence: 91%
“…Patients who developed AKI were older and had higher BMI, hypertension, severe left ventricular dysfunction, and worse preoperative renal function. Our findings aligned with the current data which report the etiology of AKICS as multifactorial [ 24 - 26 ] , correlating with advanced age, preexisting kidney disease, and left ventricular impairment, which are some of the important predictors of AKI development [ 20 ] .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in a recent study, Savluk et al. [ 28 ] reported that the prophylactic use of intravenous NAC had a protective effect on renal function in patients undergoing CABG using cardiopulmonary bypass (CPB) with pre-existing moderate renal failure. Use of CPB and pre-existing renal insufficiency might explain this difference and NAC may be effective in especial group of patients undergoing cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Use of cardiopulmonary bypass (CPB) has also been proposed to be a predictive factor for development of AKI after coronary artery bypass grafting (CABG) [19,20] . In addition to the use of prophylactic drugs [21] , knowing the predisposing factors and modifying them can help to decrease the incidence of AKI.…”
Section: Introductionmentioning
confidence: 99%